Tri Hita Karana sebagai Landasan Filosofis Pendidikan Karakter Ekologis - I Putu Agus Aryatnaya Giri; Ni Luh Ardini; Ni Wayan Kertiani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
This research is motivated by the close relationship between humans and nature which should run in harmony, but in reality it often runs in disharmony. This is due to the fact that human character and awareness in utilizing the natural environment are often blinded by excessive passions and personal interests regardless of the preservation of nature. The method used in this research is qualitative with descriptive-analytic approach. The results of the study stated that ecological awareness needs to be instilled from an early age. Ecological character education actually makes Hindu students/young generation intelligent and dignified. Smart because they are always taught about the environment and efforts to preserve it. It is dignified, because humans with ecological character are far-sighted towards the fate of the next generation, who are also entitled to a good natural heritage. In conclusion, the younger generation of Hindus must be an example of good behavior to the environment, because the philosophical concept of Tri Hita Karana will be meaningless without real action. Building quality human resources with ecological character will later become an important investment in preserving the earth as a vehicle for human existence.